Not going to give you the answer, but I'll lead you down the path.
Move "10" to the left side of the equation and sqrt(x-20) to the right side, then "square" both sides of the equation, and you'll end up with just one sqrt to contend with. Move the numbers around a bit more, and another "square" of both sides of the equation and you got "x"
2007-01-24 15:34:30
·
answer #1
·
answered by justdennis 4
·
0⤊
0⤋
i think of : sqrt(x-20) = 10 - sqrt (x) squaring the two factors yields x-20 = a hundred -20 sqrt (x) +x combining and segregating 20 sqrt(x) = one hundred twenty sqrt (x) = 6 squaring the two factors yields x =36
2016-11-27 00:29:15
·
answer #2
·
answered by ? 4
·
0⤊
0⤋
sqrt(x) + sqrt(x-20) = 10
sqrt(x-20) = 10 - sqrt(x)
square both sides
x-20 = 100 - 20sqrt(x) + x
-20 = 100-20sqrt(x)
20sqrt(x) = 100+20 = 120
sqrt(x) = 6
x = 36.
sqrt(36) + sqrt(36-20) = 10
6 + sqrt(16) = 10
6 + 4 = 10
2007-01-24 15:36:44
·
answer #3
·
answered by Tim P. 5
·
0⤊
0⤋
sqrt(x) - sqrt(x - 20) = 10
sqrt(x) = sqrt(x - 20) + 10
square both sides
x = (sqrt(x - 20) + 10)(sqrt(x - 20) + 10)
x = (x - 20) + 10sqrt(x - 20) + 10sqrt(x - 20) + 100
x = x - 20 + 20sqrt(x - 20) + 100
x = x + 20sqrt(x - 20) + 80
subtract "x" and 80 from both sides
20sqrt(x - 20) = -80
sqrt(x - 20) = -4
square both sides
x - 20 = 16
x = 36
ANS : 36
2007-01-24 17:19:48
·
answer #4
·
answered by Sherman81 6
·
0⤊
0⤋
You said minus but your wrote plus. With minus the equation is false.
the answer is x=36
2007-01-24 15:31:15
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
sqrtx - sqrt (x - 20) = 10
[sqrtx - sqrt (x - 20)]^2 = 100
x + x - 20 - 2sqrt(x^2 - 20x) = 100
2x - 20 - 100 = 2sqrt(x^2 - 20x)
2x - 120 = 2sqrt(x^2 - 20x)
x - 60 = sqrt(x^2 - 20x)
(x - 60)^2 = x^2 - 20x
x^2 - 120x + 3600 - x^2 + 20x = 0
x^2 - x^2 - 120x + 20x = -3600
-100x = -3600
x = 36
phew.
2007-01-24 15:34:32
·
answer #6
·
answered by car of boat 4
·
0⤊
0⤋